Study of stability atypical mycobacterium in relation to disinfectant preparation «Ecocid S» - Палий, А. П. (Scientific Progress & Innovations, 2012)
The results of researches of stability of atypical mycobacterium are resulted I, II, III and the IV groups on classification of Raniona to the bactericidal action of disinfectant preparation «Ecocid S». It is set as a result of the conducted researches, that atypical mycobacterium, related to the the same group on Ranionu, have a different level of stability to the action of the same disinfectant. By the most steady culture in relation to preparation «Ecocid S» there is M. fortuitum, and by the least stability – the cultures of atypical mycobacterium types of M gordonae, M. flavescens, M. triviale.